The Twits ; The minpins ; The magic finger [compact disc, unabridged] - Dahl, Roald (Penguin Group USA, 2013)
The Twits: The misadventures of two terrible old people who enjoy playing nasty tricks and are finally outwitted by a family of monkeys.